Uncovering organisational pride and psychological safety from glassdoor reviews - Ali Septiandri; Sanja Šćepanović; Marios Constantinides; Licia Capra; Daniele Quercia (EPJ Data Science)
Abstract Understanding employee experiences and attitudes is crucial for promoting a positive work environment, and enhancing engagement, satisfaction, productivity, and innovation. Organisational culture, represented by constructs like organisational pride (OP) and psychological safety (PS), captures these experiences. OP reflects employees’ emotional attachment and dedication to an organisation, while PS embodies the collective perception of safety for risk-taking and open communication. Together, these constructs offer a rich perspective, providing a top-to-bottom view of employee experiences and attitudes. To evaluate OP and PS, we developed a deep-learning framework utilising language embeddings and applied it on 430,000 employee reviews spanning 2008 to 2020, encompassing 318 major U.S. companies. Our analysis revealed significant sector-specific variations in these constructs, highlighting the unique strengths and challenges within each sector. We found that OP, which applies to the company as a whole, is high in utility and energy sectors but low in consumer and communications, while PS, which reflects the team level, is high in IT and low in communications and healthcare. Our automatic rationalisation of these organisational constructs paves the way towards the development of automated psychometric assessments at the workplace.